2020
DOI: 10.3390/ijms21165692
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/CTNNB1 Signal Transduction Pathway Inhibits the Expression of ZFP36 in Squamous Cell Carcinoma, by Inducing Transcriptional Repressors SNAI1, SLUG and TWIST

Abstract: The Wnt/CTNNB1 pathway is often deregulated in epithelial tumors. The ZFP36 gene, encoding the mRNA binding protein Tristetraprolin (TTP), is downregulated in several cancers, where it has been described to behave as a tumor suppressor. By this report, we show that Wnt/CTNNB1 pathway is constitutively activated, and ZFP36 expression is downregulated in Squamous Cell Carcinoma (SCC) cell lines compared to normal keratinocytes. Moreover, we suggest that the decrease of ZFP36 expression might depend on the activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…A b n o r m a l l e v e l s o f W n t s i g n a l i n g h a v e b e e n implicated in the development of DLBCL (23)(24)(25)(26). Many transcriptional regulators have been demonstrated to control the transcription of CTNNB1, which is a key regulator of the Wnt/β-catenin signaling pathway (27)(28)(29)(30). Previous study indicated that m 6 A mRNA methylation regulates CTNNB1 to promote the proliferation of hepatoblastoma (31).…”
Section: Discussionmentioning
confidence: 99%
“…A b n o r m a l l e v e l s o f W n t s i g n a l i n g h a v e b e e n implicated in the development of DLBCL (23)(24)(25)(26). Many transcriptional regulators have been demonstrated to control the transcription of CTNNB1, which is a key regulator of the Wnt/β-catenin signaling pathway (27)(28)(29)(30). Previous study indicated that m 6 A mRNA methylation regulates CTNNB1 to promote the proliferation of hepatoblastoma (31).…”
Section: Discussionmentioning
confidence: 99%
“…As described above, the stimulation of Wnt/β-catenin pathway results in Lef/Tcf transcription proteins activation, which was also studied in a mouse model of skin carcinogenesis: SCC was reduced by β-catenin/Tcf signaling inhibition [ 77 ]. Recently, the relationship between Wnt/β-catenin modulation and some transcription factors, such as Slug, Twist or Snail, was studied in order to evaluate the EMT role in cSCC; in particular, the gene ZFP36, encoding the Zinc-finger RNA-binding protein Tristetraprolin (TTP), was studied [ 78 ]. TTP is considered a tumor suppressor, thanks to its ability in arresting tumor growth and reducing the antitumor immune response of CD8+ lymphocytes.…”
Section: Wnt and Keratinocyte Carcinomas: From Actinic Keratosis To C...mentioning
confidence: 99%
“…TPP may revert EMT through the down-regulation of the transcription factors Slug, Twist and Snail, which may be induced by Wnt/β-catenin pathway and ZFP36 gene. Therefore, the Wnt/β-catenin pathway may further promote the EMT in cSCC [ 78 ].…”
Section: Wnt and Keratinocyte Carcinomas: From Actinic Keratosis To C...mentioning
confidence: 99%